Technics and the Human at Zero-Hour:: Margaret Atwood’s Oryx and Crake - Cooke, Grayson (Studies in Canadian Literature, 2006)
Margaret Atwood's Oryx and Crake turns on a number of myths or archetypes. With the depiction of cloned and genetically engineered life-forms and viruses comes the Frankensteinian myth of ex-utero creation coupled with its Promethean twin of forbidden knowledge and technology out of control. As befits a post-apocalyptic novel, the Last Man is invoked as survivor of the destruction and lone surveyor of all that is left, and the apocalypse is figured as a cleansing renewal making way for a millennial reign of peace. These myths are played out upon two background frameworks: of a biotechnological revisiting of post-Cold-War eschatology; and of a linguistic and literary "magic" performed by capitalist producers upon willing consumers, and by biotechnologists upon "nature." In the novel, language, writing, and thus technics are linked to the beginning and end of "life" and the "human" as they are commonly understood. Atwood's text examines the ambiguous and eschatological role of technics and biotechnology, and explores the ways in which the tekhnai of language and writing are implicated in the definition of human life.